Modified Fermions Tunneling Radiation from Nonstationary, Axially Symmetric Kerr Black Hole - Jin Pu; Kai Lin; Xiao-Tao Zu; Shu-Zheng Yang (Advances in High Energy Physics)
In this paper, by applying the deformed dispersion relation in quantum gravity theory, we study the correction of fermions’ tunneling radiation from nonstationary symmetric black holes. Firstly, the motion equation of fermions is modified in the gravitational space-time. Based on the motion equation, the modified Hamilton-Jacobi equation has been obtained by a semiclassical approximation method. Then, the tunneling behavior of fermions at the event horizon of nonstationary symmetric Kerr black hole is investigated. Finally, the results show that, in the nonstationary symmetric background, the correction of Hawking temperature and the tunneling rate are closely related to the angular parameters of the horizon of the black hole background.